ACHIEVEMENT AND STRESS PROCESSES UNDERLYING ETHNORACIAL INEQUALITIES IN HEALTH IN LATER LIFE. (11th November 2018) - Brown, T; Brown, T H
Abstract: To what extent do socioeconomic resources, stressors, and allostatic load—individually and collectively—mediate ethnoracial inequalities in self-rated health in later life? To address this question, data from the Health and Retirement Study and structural equation modeling are utilized to estimate the direct and indirect effects of race/ethnicity on health (N=10, 109). Results reveal that a majority of the effect of race on self-rated health is indirect through SES (education, income, wealth), exposure to stressors (discrimination, chronic stressors, financial strain, neighborhood disorder, traumas), and allostatic load. Collectively, indicators of achievement and stress processes explained approximately 85% of black-white and Mexican American-white inequalities in self-rated health. Findings of residual inequalities in health are consistent with growing evidence that aspects of discrimination that are often unmeasured (e.g., structural racism, and discrimination in the criminal justice system, and in housing, labor and credit markets) also contribute to ethnoracial inequalities in health.